The association of platelet to white blood cell ratio with diabetes: a nationwide survey in China - Liu, Fanglin; Wang, Tianhong; Wang, Siman; Zhao, Xiumei; Hua, Yusi (Frontiers in Endocrinology, 2024)
Background: Inflammation is integral to diabetes pathogenesis. The novel hematological inflammatory biomarker, platelet to white blood cell ratio (PWR), is linked with various conditions such as chronic kidney disease and stroke. However, the association of this novel clinical indicator with diabetes still remains unclear, which is investigated in this study.A total of 10,973 Chinese participants were included and grouped according to the tertiles of PWR (T1, T2, and T3 groups). Diagnosis of prediabetes and diabetes adhered to American Diabetes Association criteria. Binary logistic regression was adopted to assess the relationship between PWR and both diabetes and prediabetes progression. The doseresponse relationship of PWR and diabetes was examined using restricted cubic spline regression. Subgroup and interaction analyses were conducted to investigate potential covariate interactions. Results: Individuals with higher PWR had better lifestyles and lipid profiles (all P < 0.05). After adjusting for all the covariates, the T2 group had a 0.83-fold (95% CI: 0.73-0.93, P < 0.01) risk of diabetes and that for the T3 group was 0.68-fold (95% CI: 0.60-0.78. P < 0.001). Dose-response analysis identified non-linear PWR-diabetes associations in the general population and females (both P < 0.05), but absent in males. The Participants with prediabetes in the T2 and T3 groups exhibited a significant prediabetes to diabetes progressionhad lower risks of diabetes (OR = 0.80 (95% CI: 0.71-0.91for the T2 group, P < 0.001) and 0.68 (for the T3 group, 95% CI: 0.59-0.77, P < 0.001) in the full models. All the sensitivity analysis support consistent conclusions. Conclusions: An increase in PWR significantly correlates with reduced diabetes risks. A non-linear PWR-diabetes relationship exists in the general population and females, but not in males. The correlation between PWR and diabetes indicates that PWR holds potentials in early identification and prevention of diabetes.